2016
DOI: 10.2527/jas.2015-9888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth-promoting technologies on Longissimus lumborum muscle fiber morphometrics, collagen solubility, and cooked meat tenderness12

Abstract: ABSTRACT:The objective of the study was to examine the effect of growth-promoting technologies (GP) on Longissimus lumborum steak tenderness, muscle fiber cross-sectional area (CSA), and collagen solubility. Crossbred feedlot heifers (n = 33; initial BW 464 ± 6 kg) were blocked by BW and assigned to 1 of 3 treatments: no GP (CON; n = 11); implant, no zilpaterol hydrochloride (IMP; n = 11); implant and zilpaterol hydrochloride (COMBO; n = 11). Heifers assigned to receive an implant were administered Component T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 59 publications
(74 reference statements)
3
26
2
Order By: Relevance
“…In the current study, dressing percentage and yield grade were unaffected by GP treatment. In contrast, Ebarb et al (2016) reported a tendency for dressing percentage to be increased due to GP treatment, while yield grade was decreased by 28% and 33% for carcasses from heifers implanted and heifers implanted and fed ZH, respectively. Bruns et al (2005) observed similar yield grade measures, but increased dressing percentage by 0.6% for carcasses from implanted steers fed ZH when compared to non-implanted steers.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…In the current study, dressing percentage and yield grade were unaffected by GP treatment. In contrast, Ebarb et al (2016) reported a tendency for dressing percentage to be increased due to GP treatment, while yield grade was decreased by 28% and 33% for carcasses from heifers implanted and heifers implanted and fed ZH, respectively. Bruns et al (2005) observed similar yield grade measures, but increased dressing percentage by 0.6% for carcasses from implanted steers fed ZH when compared to non-implanted steers.…”
Section: Discussionmentioning
confidence: 67%
“…Quinn et al (2008) reported an increase in HCW by 2% for heifers that were not implanted, but received RH during the finishing period. Ebarb et al (2016) observed 4% heavier carcasses for heifers implanted and supplemented ZH during finishing when compared to the control heifers. In the current study, dressing percentage and yield grade were unaffected by GP treatment.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations